Resíduos dos valores morais cristãos da idade média na obra Helena, de Machado de Assis - Pereira, Adalucami Menezes (2010)
This research, linked to on line literature and history, aims to highlight the presence of Christian moral values present in the work Helena by Machado de Assis. Through the Theory of Residuality, we intend to demonstrate the cultural, ideological and hysterical received by our people, especially when it concerns me to Roman Catholic beliefs. However, we intend to prove these manifestations are remnants of the medieval mindset of the thirteenth century. Submitted by waste, that mentality led to a hybrid imagery that colonized the moral thinking of our country. It is also our intention to prove that the novel Helena highlights the virtues of the characters of the plot, as a way of perpetuating these moral values. Finally, emphasizing the behavior of the protagonist Helen, as an example of dignity unblemished.